Claudin18.2 defines a prognostically distinct subgroup of intrahepatic cholangiocarcinoma via CD8+ T-cell exclusion - Yu, Chengui; Pan, Yuren; Li, Fuli; Guo, Zhenyun; Xu, Da; Zhu, Ying; Yin, Baobing (Frontiers in Oncology, 2025)
Background and purposeIntrahepatic cholangiocarcinoma (ICC) is an aggressive malignancy with limited therapeutic options. Claudin18.2 (CLDN18.2), a tight junction protein aberrantly expressed in gastrointestinal cancers, has not been systematically evaluated in ICC. This study investigates CLDN18.2’s expression, clinical relevance, and interplay with the tumor immune microenvironment (TIME) in ICC.MethodCLDN18.2 expression was analyzed in 83 ICC and 47 matched non-tumor tissues on tissue microarray sections using immunohistochemistry (IHC). Bioinformatics validation utilized ArrayExpress (E-MTAB-6389) and GEO (GSE119336, GSE107943, GSE89749, GSE32225) datasets. Clinicopathological correlations, survival analysis, and CD8+ tumor-infiltrating lymphocytes (TILs) quantification were performed.ResultsCLDN18.2 was exclusively expressed in 24.1% (20/83) of ICC tissues, absent in non-tumor tissues. Positive CLDN18.2 expression correlated with elevated serum CA19-9 (P = 0.026), smaller tumor size (P = 0.03), unifocality (P = 0.03), and higher recurrence (P = 0.018). Multivariable analysis identified CLDN18.2 as an independent prognostic factor for reduced overall survival (OS: HR = 2.555, 95% CI = 1.250–5.223, P = 0.01) and disease-free survival (DFS: HR = 2.229, 95% CI = 1.125–4.415, P = 0.022). Single-sample gene set enrichment analysis (ssGSEA) analysis revealed an inverse correlation between CLDN18 expression and CD8+ T cells (P = 0.012), while IHC showed a trend toward negative correlation between CLDN18.2 expression and CD8+ TILs density (P = 0.12). Combined stratification showed optimal OS in CLDN18.2-/CD8high patients versus worst outcomes in CLDN18.2+/CD8low subgroup (P = 0.006).ConclusionsCLDN18.2 is a tumor-specific prognostic biomarker in ICC, marking aggressive subsets with early recurrence. Combined CLDN18.2/CD8+ TILs stratification enhances prognostic precision and suggests synergistic potential for CLDN18.2 targeted therapies with immunomodulation. These findings warrant clinical validation to guide personalized treatment strategies.